PEMBERIAN PUPUK KULIT PISANG RAJA (Musa sapientum) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Prelly Tuapattinaya; Feby Tutupoly (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Backgroud: Cayenne pepper or Capsicum frutescens L. is a plant wich very popular all over the world. Banana peel has been considered as garbage and smells, there are many chemicals that contain elements of potassium, phosphorus, magnesium, potassium, and sodium brpotensi to be used as fertilizer. Method: This study used a randomized block design (RBD) with treatment carried out in the form of fertilizers Plantain skin (P). Fertilization Plantain skin consists of four stage treatment, namely: P0 (0 ml/polybag), P1 (200 ml/polybag), P2 (350 ml/polybag), P3 (500 ml/polybag). From the observed level of treatment, three replications were made so that there are 12 samples in the study. Results: Cayenne pepper plant growth with the highest value on plant height, number of leaves and number of branches acquired in treatment P3 (500 ml fertilizer plantain skin ). While the generative period banana peels fertilizer treatments showed that there is a significant influence on the production of fruit and weeks 8, 10 and 12 and the weight of the fruit at harvest time. The number of pieces of cayenne pepper with the highest value obtained in treatment P3 (500 ml fertilizer plantain skin). Conclusion: Treatment P3 (500ml fertilizer plantain skin) is a treatment wich best during the vegetative growth of plant height, number of leaves and number of branches cayenne pepper. Moreover P3 is also the best treatment on fruit number and fruit weight during the generative crop.